(untitled) (Perner’s Contacts, 2009)
This article describes the positive environmental impacts of roundabouts on their surroundings, particularly in terms of noise pollution. Main purpose of the article is to present the objectification of impact of reconstructing the intersections to roundabouts in urban areas of the Slovak Republic and the Czech Republic.environmental impacts.